EFEKTIVITAS APLIKASI BIOCHAR TEMPURUNG KELAPA PADA MEDIA TANAM TERHADAP PERTUMBUHAN DAN SERAPAN HARA N DI PEMBIBITAN UTAMA KELAPA SAWIT (Elaeis guineensis Jacq.) - Sri Murti Tarigan; Tifany Zia Aznur; Rafika Umami (Jurnal Agro Estate, 2021)
This study was conducted to determine the effect of application of coconut shell biochar on planting media on the growth and uptake of leaf and soil nutrients in oil palm main nurseries. To get good and healthy seeds, soil conditioner is also needed to increase land productivity. One of the soil improvement materials is biochar. This research was conducted in the STIPAP Medan experimental garden. This research was conducted for 6 months. Starting in August 2020 - February 2021. This study used a Factorial Randomized Block Design (RAK) method consisting of 9 treatments with 4 replications, so the total sample was 36 seedlings. Parameters observed were seedling height, stem diameter, number of leaves, shoot dry weight, root dry weight and nutrient N content in leaves and soil. The data obtained were analyzed statistically by analysis of variance (ANOVA) with the F test. The results of this study indicate that the application of coconut shell biochar and compound fertilizer in oil palm nurseries can use the best combination dose of 1.8 kg of biochar and 75% compound fertilizer of the dose. The standard gave several significant and very significant effects on stem height, stem diameter, number of leaves, shoot dry weight and root dry weight. And the interaction of coconut shell biochar treatment and compound fertilizer did not significantly affect all observation parameters.